Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1097/jgp.0b013e3181987747
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Older Adults With Generalized Anxiety Disorder

Abstract: Objectives-The purposes of this study are to determine the frequency and severity of insomnia symptoms and related complaints experienced by older adults with GAD and compare them with older adults without GAD; compare insomnia symptoms among older adults with GAD with and without comorbid depression; determine if there are age differences in insomnia severity among people with GAD; and determine if there are differences in insomnia severity between older adults with GAD and older adults diagnosed with insomni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 19 publications
6
55
0
4
Order By: Relevance
“…Moreover, regarding anxiety, Brenes et al [39] found similar results to our findings. They found that elderly individuals with generalized anxiety disorder (GAD) with or without comorbid depression reported significantly higher insomnia severity, and there were no differences in sleep disturbances between older adults with GAD only and older adults with comorbid GAD and depression.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, regarding anxiety, Brenes et al [39] found similar results to our findings. They found that elderly individuals with generalized anxiety disorder (GAD) with or without comorbid depression reported significantly higher insomnia severity, and there were no differences in sleep disturbances between older adults with GAD only and older adults with comorbid GAD and depression.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently assessing sleep disturbances in older adults could be a key diagnostic indicator of psychological difficulties [23], but must be differentiated from sleep disturbances due to medical conditions. Brenes et al [24] found 90% of older adults with GAD reported dissatisfaction with sleep, and 52% -68% experienced moderate to severe insomnia. Sleep onset and maintenance difficulties were most common in older adults with GAD, followed by early morning wakening and initial insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…At an individual level, anxiety symptoms and disorders have been found to be associated with increased sleep disturbance (Brenes et al, 2009), intake of anxiety related medication (Gonç alves, Pachana, & Byrne, 2011), disability (Brenes et al, 2005), mortality (Ostir & Goodwin, 2006), and decreased cognitive functioning (Beaudreau & O'Hara, 2009;Mantella et al, 2007). At a societal level, late-life anxiety was related to increased use of health services, namely longer appointments with physicians (Stanley, Roberts, Bourland, & Novy, 2001), and inability to perform daily functions (Trollor, Anderson, Sachdev, Brodaty, & Andrews, 2007).…”
Section: Introductionmentioning
confidence: 96%